Effect of Slightly Acidic Electrolyzed Water on Chlorophyll Degradation in Postharvest Broccoli - HAN Ying, SUN Ying, GUO Feng, WANG Xinyu, ZHAO Anqi, WU Zhaoxia, LI Pengxia, LI Guofeng, HU Huali (Shipin Kexue, 2023)
To explore the effect of slightly acidic electrolyzed water (SAEW) on chlorophyll degradation in postharvest broccoli, the pattern of changes in the color, total chlorophyll content, chlorophyll derivative content, chlorophyll degrading enzyme activities, and key chlorophyll metabolism-related gene expression of postharvest broccoli after treatment with 50 mg/L SAEW was analyzed. The results showed that SAEW treatment could effectively slow down the degradation of total chlorophyll, maintain the contents of chlorophyll derivatives chlorophyll a, chlorophyll b, chlorophyllide a, chlorophyllide b, pheophorbide a, and pheophytin a, and delay the increase in the activities of chlorophyll metabolizing enzymes, Mg-dechelatase, pheophytinase, and pheophorbide an oxygenase in postharvest broccoli. Meanwhile, it significantly inhibited the expression of the genes encoding chlorophyll b reductase, chlorophyllase 1, chlorophyllase 2, chlorosis protein, pheophytinase, pheophorbide an oxygenase, red chlorophyll catabolite reductase, and aging specific cysteine protease, thereby allowing color protection and freshness preservation. In conclusion, SAEW can be used as an effective method to delay postharvest chlorophyll degradation and inhibit yellowing and senescence in broccoli.